Secretion of the disulphide bond generating catalyst QSOX1 from pancreatic tumour cells into the extracellular matrix: Association with extracellular vesicles and matrix proteins. Issue 7 (2nd July 2022) - Millar‐Haskell, Catherine S.; Sperduto, John L.; Slater, John H.; Thorpe, Colin; Gleghorn, Jason P.
Abstract: Quiescin sulfhydryl oxidase 1 (QSOX1) is a disulphide bond generating catalyst that is overexpressed in solid tumours. Expression of QSOX1 is linked to cancer cell invasion, tumour grade, and aberrant extracellular matrix (ECM) protein deposition. While the secreted version of QSOX1 is known to be present in various fluids and secretory tissues, its presence in the ECM of cancer is less understood. To characterize secreted QSOX1, we isolated extracellular vesicles (and particles) (EV(P)s) from conditioned media using ultracentrifugation and separated the supernatant using tangential flow filtration. We discovered that most of the secreted QSOX1 resides in the EVP‐depleted supernatant and in the soluble protein fraction. Very little QSOX1 could be detected in the EVP fraction. We used immunofluorescence to image subpopulations of EVs and found QSOX1 in Golgi‐derived vesicles and medium/large vesicles, but in general, most extracellular QSOX1 was not attributed to these vesicles. Next, we quantified QSOX1 co‐localization with the EV marker Alix. For the medium/large EVs, ∼98% contained QSOX1 when fibronectin was used as a coating. However, on collagen coatings, only ∼60% of these vesicles contained QSOX1, suggesting differences in EV cargo based on ECM coated surfaces. About 10% of small EVs co‐localized with QSOX1 on every ECM protein surface except for collagen (0.64%). We next investigated adhesion of QSOX1 to ECM proteins in vitro and in situ and found that QSOX1 preferentially adheres to fibronectin, laminins, and Matrigel compared to gelatin and collagen. This mechanism was found to be, in part, mediated by the formation of mixed disulphides between QSOX1 and cysteine‐rich ECM proteins. In summary, we found that QSOX1 (1) is in subpopulations of medium/large EVs, (2) seems to interact with small Alix+ EVs, and (3) adheres to cysteine‐rich ECM proteins, potentially through the formation of intermediate disulphides. These observations offer significant insight into how enzymes, such as QSOX1, can facilitate matrix remodelling events in solid tumour progression.